Protective effects of functional powdered beverage containing Cassumunar ginger (Zingiber cassumunar Roxb.), soybean (Glycine max), and cinnamon (Cinnamomum burmannii) against hyperlipidemia and injuries of liver and kidney in high-fat-diet rats - Nurkhasanah Mahfudh; Ika Dyah Kumalasari; Nanik Sulistyani; Candra Azzahra; Salma Dewina Salimah; Suryati Suryati; Zainul Amiruddin Zakaria (Science Society of Thailand, 2024)
A high-fat consumption can cause hyperlipidemia, which is marked by an increase of total cholesterol, triglycerides, and low-density lipoprotein (LDL); and a decrease of high-density lipoprotein (HDL) in serum. This condition can lead to various degenerative diseases. This study aimed to observe the effects of functional powdered beverage (FPB) on levels of cholesterol, triglyceride, blood urea nitrogen (BUN), and creatinine; SGOT and SGPT activities; and liver histopathology in rats given a high-fat diet (HFD). The FPB was made of Zingiber cassumunar rhizome, soybean, and cinnamon. Test animals were divided into six groups: normal, negative control, positive control, and three treatment groups. While the normal group was received only a standard diet, the other five groups were received HFD along the studies. In addition, the three treatment groups were treated with different doses of FPB of 1000, 1500, and 2000 mg/kg BW, respectively. Biochemical parameters were measured with UV-Vis spectrophotometry, and histopathological observations used hematoxylin and eosin (H&E) staining. The data were analyzed statistically at a 95% confidence level using SPSS. In comparison to the negative control, the results demonstrated a statistical reduction in cholesterol, triglycerides, BUN, and creatinine levels (p < 0.05), indicating the effect of the functional powdered beverage as an antihyperlipidemic agent and protection for hyperlipidemia-associated kidney injuries. SGOT and SGPT activities were also lowered significantly (p < 0.05) in comparison to the negative control, suggesting a hepatoprotective effect of the beverage in HFD. Improved liver histology and decreased hepatosomatic index (HI) in the three treatment groups attested to the beverage’s hepatoprotective activity, with the best pharmacological effects obtained at 2000 mg/kg BW.